2022
DOI: 10.21203/rs.3.rs-1820580/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The gametogenic cycle and spawning of the Short-Necked Clam, Paphia undulata Born, 1778 from Timsah Lake, Suez Canal, Egypt

Abstract: Background The Short-Necked Clam Paphia undulata is a marine edible bivalve consumed all over the world and locally in Egypt. In the past decade, its population declined across the Egyptian fisheries due to overexploitation and pollution. The gametogenic cycle and spawning studies of P. undulata were carried out during the period from January 2020 to December 2020 along Timsah Lake, Suez Canal, Egypt. Results Shell lengths of the collected clams ranged from 2.31 cm to 6.22 cm in males, 2.05 cm to 5.97 cm in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The results of the maturation cycle of S. Senilis at both sites showed that spawning takes place throughout the year. This is typical behavior for bivalves in tropical zones (Mahmoud and Yassien, 2022;Manjarrés-Villamil et al, 2013;Narasimham, 1988;Toral-Barza and Gomez, 1985). This is consistent with the results of Le Loeuff and Zabi (1993), who reported the year-round presence of S. senilis larvae in the Lagos lagoon in Nigeria.…”
Section: Reproductive Phenologymentioning
confidence: 67%
“…The results of the maturation cycle of S. Senilis at both sites showed that spawning takes place throughout the year. This is typical behavior for bivalves in tropical zones (Mahmoud and Yassien, 2022;Manjarrés-Villamil et al, 2013;Narasimham, 1988;Toral-Barza and Gomez, 1985). This is consistent with the results of Le Loeuff and Zabi (1993), who reported the year-round presence of S. senilis larvae in the Lagos lagoon in Nigeria.…”
Section: Reproductive Phenologymentioning
confidence: 67%
“…The Mahmoud and Yassien (2023). These stages were identified by examining the size and density of different germ cells, which originate from gametogenesis stem cells in the gonad.…”
Section: Gametogenesismentioning
confidence: 99%